Influence of Maleinized Polybutadiene on Adhesive Strength and Toughness of Epoxy Resins - Mohammed Panthakkal Abdul Muthalif; Youngson Choe (International Journal of Polymer Science)
This study explored the effect of maleinized polybutadiene (MPB) on the mechanical properties of epoxy resins. Diglycidyl ether of bisphenol-A, an epoxy resin, was modified by incorporating MPB having different molecular weights in order to improve the fracture toughness and peel strength. MPB was mixed with epoxy resin at several concentrations (5, 10, and 15 phr), with the epoxy resin as the major phase and MPB as the minor phase. A comparative study was performed to investigate the influence of MPB on epoxy resins based on their molecular weight difference. Lap shear test results showed that the shear strength of the MPB-modified epoxy resins was superior to that of the neat epoxy resin. At 10 wt% MPB loading, the modified epoxy resin exhibited an 87% enhancement in T-peel strength relative to that of the neat epoxy resin. Moreover, the fracture energy of the modified epoxy system increased proportionally with the amount of MPB in the epoxy matrix. These results indicate that MPB incorporation is a simple and effective method for designing multifunctional epoxy resins, thus facilitating their industrial application in various spheres.